2012
DOI: 10.5093/cl2012a14
|View full text |Cite
|
Sign up to set email alerts
|

Problemas Emocionales y Comportamentales en Niños Adoptados y No Adoptados

Abstract: Resumen. El objetivo de este trabajo es conocer si niños y niñas adoptados manifiestan problemas emocionales y comportamentales en distinta medida que sus iguales no adoptados. Se analiza la manifestación de problemas, según la versión del profesorado, en un total de 569 chicos y chicas de entre 7 y 16 años de edad. Se establecen tres grupos de comparación de niños no adoptados. Los resultados muestran que los adoptados manifiestan, como media, más problemas que sus actuales compañeros de aula. Los mayores pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 28 publications
1
8
0
5
Order By: Relevance
“…The female adoptees’ psychological adjustment was more similar to that of their nonadopted peers, because there were no significant group differences in SOM, DEP, and PHOB subscales or in the PSDI. These findings are especially relevant considering the results of these participants in Wave 2 (15 years ago), when female adoptees showed greater behavioral and inattention problems in comparison to their classmates (large effect sizes) than did male adoptees in relation to their classmates (Sánchez-Sandoval, & Palacios, 2012). In adulthood, the differences between female adoptees and their peers have been reduced with respect to previous life stages (childhood and adolescence).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The female adoptees’ psychological adjustment was more similar to that of their nonadopted peers, because there were no significant group differences in SOM, DEP, and PHOB subscales or in the PSDI. These findings are especially relevant considering the results of these participants in Wave 2 (15 years ago), when female adoptees showed greater behavioral and inattention problems in comparison to their classmates (large effect sizes) than did male adoptees in relation to their classmates (Sánchez-Sandoval, & Palacios, 2012). In adulthood, the differences between female adoptees and their peers have been reduced with respect to previous life stages (childhood and adolescence).…”
Section: Discussionmentioning
confidence: 90%
“…There are two contradictory viewpoints about development: one that defends adoption as a context for recovery from early adversity and one that defends the persistence of its effects (Rushton, 2014). As mentioned earlier, previous studies have shown more difficulties in adoptees in comparison to nonadoptees, but it has been revealed that adoptees have a better adjustment than do children in the foster care system (Sánchez-Sandoval & Palacios, 2012). Juffer et al (2011) showed that after adoption, children experienced an important recovery from their initial delays in development.…”
Section: Psychological Adjustment In Adult Adopteesmentioning
confidence: 94%
See 1 more Smart Citation
“…No obstante, aunque no hay datos definitivos al respecto, parece que los niños post-institucionalizados procedentes de adopción internacional, especialmente en los adoptados de más de tres años de edad, pueden mostrar trastornos de conducta de tipo externalizante (Núñez, 2008). Gran parte de estos niños y niñas experimentan dificultades en las relaciones interpersonales y/o sus relaciones son deficitarias y/o inadecuadas, de forma que o lo pasan mal al interactuar con otras personas, o en sus relaciones hacen sufrir a los demás (Sánchez-Sandoval y Palacios, 2012).…”
Section: Posibles Necesidades Específicas De Apoyo Educativounclassified
“…Although there is a great amount of research on adopted children's and adolescent adjustment, including important meta-analysis, studies with Spanish samples are limited (Aramburu et al, 2020;Barcons et al, 2011;Berástegui, 2007Berástegui, , 2010Berástegui y Rosser, 2012;Fuentes et al, 2004;Sánchez-Sandoval & Palacios, 2012), despite the relevance of cultural issues in the shaping of the adoptive experience and child behavior (Barni et al, 2012;Masha et al, 2007) and the relevance of Spain in the international adoption scene in recent decades (Selman, 2009).…”
Section: Introductionmentioning
confidence: 99%